2018
DOI: 10.1103/physreva.97.043422
|View full text |Cite
|
Sign up to set email alerts
|

Spin-interaction effects for ultralong-range Rydberg molecules in a magnetic field

Abstract: We investigate the fine and spin structure of ultralong-range Rydberg molecules exposed to a homogeneous magnetic field. Each molecule consists of a 87 Rb Rydberg atom whose outer electron interacts via spin-dependent s-and p-wave scattering with a polarizable 87 Rb ground state atom. Our model includes also the hyperfine structure of the ground state atom as well as spin-orbit couplings of the Rydberg and ground state atom. We focus on d-Rydberg states and principal quantum numbers n in the vicinity of 40. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This should be fairly straightforward to accomplish, and it will have a significant impact on the practicality of including spin into a study of polyatomic molecules. As the present moment the enlarged Hilbert space including the hyperfine structure of each perturber rapidly increases the basis size needed for diagonalization [202,196], and the massive reduction in basis size within the trilobite overlap approach would dramatically reduce the computational effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should be fairly straightforward to accomplish, and it will have a significant impact on the practicality of including spin into a study of polyatomic molecules. As the present moment the enlarged Hilbert space including the hyperfine structure of each perturber rapidly increases the basis size needed for diagonalization [202,196], and the massive reduction in basis size within the trilobite overlap approach would dramatically reduce the computational effort.…”
Section: Discussionmentioning
confidence: 99%
“…[193] investigated these potential energy surfaces and alignment in an electric field, while Refs. [194,195,196,197] concentrate on magnetic fields effects. These studies showed that the strong coupling to external fields can prove destructive to LRRMs, as the Zeeman splitting can eliminate the trilobite states [194].…”
Section: Influence Of Fields On Electronic Potential Energy Curvesmentioning
confidence: 99%
“…For L p = 0 there is s-wave interaction, while p-wave interaction is given for L p = 1. We employ a generalized Fermi pseudopotential [7,40]…”
Section: A Potential Energy Curvesmentioning
confidence: 99%
“…Comparison to experimental photoassociation spectra (blue and black dots) confirms the alignment mechanism and allows one to associate the experimental signals to different molecular geometries. Quantative corrections due to spin-spin and spin-orbit interactions have been in the focus of [8] and will be discussed in Sec. VI.…”
Section: Field Controlmentioning
confidence: 99%